El servicio de provisión de agua potable y saneamiento como servicios esenciales - Mendoza Flores, Santos Ernesto (2016)
The author starts by revising the concept of public service, highlighting the idea of publicatio as an important element. With this taken into consideration, he points out that it is not possible to understand the concept of public service without the presence of ownership by the State. In this context, the concept of essential service arises as a technique that harmonizes social demands and the traditional conception of public service. All in all, these concepts are materialized to affirm that the nature of the service of drinking water and sanitation is of essential service, developing and applying its principles to the concrete case.